The Grass is Always Greener on the Other Side, or Else Austria Through the Eyes of European Rural Developers - Katalin Mezei; Szabolcs Troján; Nóra Lipcseiné Takács (DETUROPE)
The study seeks to answer the question as to why the combined performance of agriculture and forestry can be explained by the fact that in an EU member state with an agricultural disadvantage and with an advanced economy, the size of the cultivated area is high. The reasons are complex and suggest a deliberately chosen strategy, the essence of which is that in Austria the social perception of agriculture is far more favorable than it would be expected from its GDP contribution. The reasons for this are partly rooted in the history of the past, but may also be linked to a more immediate and strategic decision making primarily on the transformation of the agricultural product structure, the efficient use of resources from the EU, the use of sophisticated tools for rural tourism and, last but not least, on the widespread shaping of the attitudes of the population.